2019
DOI: 10.1111/jfpp.14187
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Brazilian pepper ( Schinus terebinthifolius Raddi) extracts on color and oxidative stability of sardine patties stored under refrigeration

Abstract: This study investigated the effect of Brazilian pepper (Schinus terebinthifolius Raddi) extracts obtained by microwave‐assisted extraction on the color and oxidative stability of sardines stored under refrigeration during 9 days. The increase in pH was less pronounced in PC (100 ppm of butylated hydroxytoluene), BPP1 (100 ppm of Brazilian pepper in 70% ethanol), and BPP2 (100 ppm of Brazilian pepper in 70% acetic acid). PC and BPP1 showed the lowest lightness and lipid oxidation, and the highest metmyoglobin r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 67 publications
(100 reference statements)
0
2
0
Order By: Relevance
“…peel during 10 days of storage at 4 ± 1°C under aerobic package lamb burgers Guedes-Oliveira et al (2018). observed that Myrciaria dubia peel and seed extracts (100 ppm) increased the lipid stability in ground lamb stored at 4°C for 9 days when compared to control and BHT counterparts; however, no positive effect on protein oxidation was observed Fortunato et al (2019). reported a similar effect of Brazilian pepper (Schinus terebinthifolius Raddi) extract and BHT, both at 100 ppm, against lipid oxidation in refrigerated sardines during 9 days,…”
mentioning
confidence: 98%
“…peel during 10 days of storage at 4 ± 1°C under aerobic package lamb burgers Guedes-Oliveira et al (2018). observed that Myrciaria dubia peel and seed extracts (100 ppm) increased the lipid stability in ground lamb stored at 4°C for 9 days when compared to control and BHT counterparts; however, no positive effect on protein oxidation was observed Fortunato et al (2019). reported a similar effect of Brazilian pepper (Schinus terebinthifolius Raddi) extract and BHT, both at 100 ppm, against lipid oxidation in refrigerated sardines during 9 days,…”
mentioning
confidence: 98%
“…These compounds are generally rich in phenolic substances (e.g., phenolic acids, flavonoids, tocopherols, lignins, and tannins), implying their main antioxidant, antibacterial, and antifungal activities in various food systems. On the other hand, controlling the stability of these compounds is still a challenge for scientific researchers and the food industry, since high exposure to the processing temperature of packaging materials can degrade the active compounds, limiting their industrial application (Fortunato et al., 2019; Liang et al., 2022).…”
Section: Overview Of Natural Antioxidants Applied In Nanocompositesmentioning
confidence: 99%